1. The problem statement, all variables and given/known data All married couples have fights 2. Relevant equations let x be a person and y be another person M(x,y): x is married to y F(x,y): x have fought y 3. The attempt at a solution ∀x∃y(M(x, y) → F(x, y)): i read my translation as "For all x, there is some y such that if x is married to some y then x and y have fought each other" but i found the correct translation to be: ∀x∀y(M(x, y) → F(x, y))... I do not understand where my mistake is. Should the interpretation for using ∀y be for all the partners x had and will ever have?